Women in the Story of Jesus: The Gospels through the Eyes of Nineteenth-Century Female Biblical Interpreters - Taylor, Marion Ann (Wm. B. Eerdmans Publishing Co, 2016)
Title Page -- Copyright -- Table of Contents -- Acknowledgments -- A Note on References and Editors' Additions -- Introduction -- PART 1 HEART AND HANDS: WOMEN'S SPIRITUALITY -- 1. Mary: The Exemplary Disciple -- Clara Lucas Balfour: Humility: The Noblest Virtue -- Elizabeth Stuart Phelps: Receiving the Divine -- Sarah Trimmer: Blessed Humility -- Gracilla Boddington: Worshipping with Mary -- Mary Anne SchimmelPenninck: Hail Her as the Woman -- Elizabeth Wordsworth: Cleopatra or Mary? -- Christina Georgina Rossetti: The Veiled Virgin -- Elizabeth Rundle Charles: Communion and Sacrifice -- 2. Mary and Martha of Bethany: Spirituality in the Workplace -- Esther Hewlett Copley: Consecrated Abilities -- Clara Lucas Balfour: Action and Contemplation -- Nina L. McFadyen: The Happy Home in Bethany -- Etty Woosnam: Meddlesome Matty -- M. G.: Work and Devotion -- Mary Ann Smith: Doing What We Can -- PART 2 UNSEALED LIPS: WOMEN PREACHING -- 3. Anna: The Vocation of a Woman Preacher -- Sarah Hale: Anna's Spiritual Superiority -- Elizabeth Baxter: A Role Model for Female Ministry -- Elizabeth Wilson: A Woman with a Vocation -- M. G.: A Widow's Vocation: A Sermon -- 4. The Woman at the Well: The First Samaritan Evangelist -- Clara Lucas Balfour: A Changed Woman -- Elizabeth Baxter: The Gospel Preacher -- Phoebe Palmer: Women's Preaching Justified -- Hannah Jane Locker-Lampson: Empathetic Evangelistic Preaching: A Sermon -- Mary Elizabeth Beck: Bearing the Words of Life: A Sermon -- 5. Herodias and Salome: The Royal Tigresses Judged -- Harriet Beecher Stowe: It's All about Power -- Euphemia Johnson Richmond: Voluptuous Dancing -- Mrs. Donaldson: The Great Danger of Worldly Amusements: A Sermon -- Margaret Black: Pleasing the Tyrant -- PART 3 UNVEILED EYES: WOMEN AND THE BIBLICAL TEXT -- 6. A Woman of Canaan: Experiencing the Text